Bronchoscopic Laser Interstitial Thermal Therapy: An Experimental Study in Normal Porcine Lung Parenchyma. Issue 4 (October 2018) - Casal, Roberto F.; Walsh, Garrett; McArthur, Mark; Hill, Lori R.; Landaeta, Maria F.; Armas Villalba, Aristides J.; Ong, Philip; Debiane, Labib; Vakil, Erik; Grosu, Horiana B.; Jimenez, Carlos A.; Ost, David; et al.
Abstract : Background: Population aging and lung cancer screening strategies may lead to an increase in detection of early-stage lung cancer in medical inoperable patients. Recent advances in peripheral bronchoscopy have made it a suitable platform for ablation of small peripheral tumors. Methods: We investigated the tissue-ablative effect of a diode laser bronchoscopically applied by a laser delivery fiber (LDF) with wide aperture on porcine lung parenchyma. Laser was tested ex vivo and in vivo to identify the most effective power settings and LDF. Chest computed tomography (CT) were obtained immediately after ablation and after 3 days of observation. At day 3, necropsy was performed. Results: On the basis of our ex vivo and in vivo experiments, we selected the round-tip LDF to be activated at 25 W for 20 seconds. Ten ablations were performed in 5 pigs. One ablation resulted in a pneumothorax requiring aspiration. All animals remained stable for 72 hours. CT findings at days 1 and 3 showed an area of cavitation surrounded by consolidation and ground glass. Median size of CT findings (long axis) was 26 mm (range, 24 to 38) at day 1, and 34 mm (range, 30 to 44) at day 3. Necropsy showed an area of central char measuring from 0.8×0.7×0.9 cm to 2.4×3.5×1.2 cm, surrounded by a gray-brown to dark red area. On histology, variable degrees of necrosis were evident around the charred areas. Conclusion: Bronchoscopic laser interstitial thermal therapy can achieve relatively large areas of ablation of normal lung parenchyma with a low rate of periprocedural complications.